Pernikahan Sesama Jenis: Tinjauan Hak dan Kewajiban Berdasarkan Undang-Undang Perkawinan - Rani Nuraeni; Maruli Tua Tampubolon; Atmoro Atmoro; Habib Habib; Totok Handono (Syntax Corporation Indonesia, 2024)
In the context of Indonesian law, marriage is defined as a bond between a man and a woman, which explicitly closes the possibility of recognition of same-sex marriage. In the midst of international developments that increasingly recognize the rights of same-sex couples, Indonesia still maintains a conservaative view influenced by religious and social norms. This study aims to analyze Indonesia’s Law No. 16 of 2019 on Marriage in the context of the rights and obligations of married couples and whether there is potential recognition for same-sex marriage in Indonesia. The law defines marriage as a union between a man and a woman, excluding the possibility of recognizing same-sex marriages. The study employs normative legal research with legislative and conceptual approaches. The findings reveal that provisions such as the minimum age for marriage, dispensation, and marriage authorization are only applicable to heterosexual couples. The rights established in the law, including protection from violence and access to healthcare, do not cover same-sex couples due to the absence of legal recognition. The conclusion emphasizes the existing inequality in access to civil rights in Indonesia, particularly for the LGBT community. While challenges remain from conservative social and religious norms, discussions on potential future revisions to marriage law remain open, particularly within the framework of equality and non-discrimination.